(untitled) (Gestão & Regionalidade, 2023)
Purpose: Social Network Analysis (ARS) can be applied as a tool for understanding relationships and connections, if in the network there are business exchanges such as offerors and buyers among the members of the group of microentrepreneurs. Thus, the objective of this research is to analyze the network of interactions of a group of microentrepreneurs of a residential condominium in São Paulo in times of Covid-19, with support in the theoretical approach of social network analysis. Originality / value: article studies the adoption of social media analysis in microentrepreneurs’ businesses, little explored on the subject in an integrated way. Design / methodology / approach: Descriptive and exploratory study with in-depth analysis using social network analysis techniques, complemented by simple regression analysis. Findings: It was verified that the objective of the study was to analyze the network of interactions of a group of microentrepreneurs of a residential condominium in São Paulo in times of Covid-19, with support in the theoretical approach of analysis of social networks. According to the data obtained, in the group of microentrepreneurs it is possible to identify that there is a very strong relationship between the actors of the network, with few actor’s hub type, expanding the exchange of information within the network, as expected in the objective of this article